Peran Koping Religius terhadap Kesehatan Mental dan Kesejahteraan Psikologis Caregiver: Sebuah Literature Review - Siska Puspitasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to identify the role of religious coping in the mental health and psychological well-being of caregivers of chronic illness patients, including cancer, dementia, mental disorders, and stroke, to inform the development of psychological support programs that integrate spiritual values. A literature review method was employed on ten scientific articles published between 2021 and 2025, retrieved from Google Scholar, Garuda, ResearchGate, and other databases, selected based on their relevance to religious coping and caregiver mental health, then analyzed, compared, and synthesized to summarize substantive findings. The results show that religious coping functions as an adaptive psychological resource used relatively universally by caregivers across populations, although its impact depends on its valence, negative religious coping is consistently associated with higher caregiver burden, while positive religious coping does not always significantly affect burden and only explains a small proportion of variance in adaptation, despite playing an important role as a mediator or predictor in certain populations. It is concluded that religious support should be positioned as one component within a holistic approach combined with material, social, and other psychological support, accompanied by assessment of religious coping types and cross-disciplinary collaboration between clinical practitioners and religious leaders to sustainably support caregiver mental health.